Synoptic and Climatological Analysis of Autumn 2023 from the Perspective of a Meteorologist Forecaster - Fania SFÎRLEAZĂ; Adriana POPA; Adriana BĂCESCU (Aerul şi Apa: Componente ale Mediului, 2024)
The fall of 2023 was atypical both in terms of recorded temperatures and accumulated precipitation. September and October retained many characteristics of an authentic summer, with this year experiencing up to 22 summer days, 16 tropical days, and 3 heatwave days. The weather conditions this autumn were influenced by the atypical position and evolution of baric centers, as well as the warm advection at the 500hPa level